1977
DOI: 10.1073/pnas.74.12.5584
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-induced linkages of plasma membrane proteins to intracellular actomyosin-containing filaments in cultured fibroblasts.

Abstract: The surface distributions of three different membrane integral proteins, #2-microglobulin (part of the histocompatibility antigen complex), aminopeptidase (a-aminoacyl-peptide hydrolase; EC 3.4.11.2), and the Na+,K+-ATPase (ATP phosphohydrolase; EC 3.6. The idea that cell surface molecules can interact with intracellular cytoskeletal proteins has been widely entertained (for reviews see refs. 1-3). Until recently, however, the primary evidence for this has been indirect, based on the effects of drugs such as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(97 citation statements)
references
References 26 publications
3
94
0
Order By: Relevance
“…Furthermore, the detailed investigation of the capping process revealed a transmembranal connection of cell surface proteins with intracellular structures, especially with contractile elements (Putter & Mannweiler,I973,I976,I977). A close morphological neighbourhood of patches with actin-myosin filaments and the co-capping of cell surface antigens with actin-myosin have been demonstrated (Ash et al 1977;Gabbiani et al 1977). Thus the patching and capping phenomena could be looked at as part of a transmembranal information system which may trigger intracellular events at the moment of adsorption of a multivalent ligand to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the detailed investigation of the capping process revealed a transmembranal connection of cell surface proteins with intracellular structures, especially with contractile elements (Putter & Mannweiler,I973,I976,I977). A close morphological neighbourhood of patches with actin-myosin filaments and the co-capping of cell surface antigens with actin-myosin have been demonstrated (Ash et al 1977;Gabbiani et al 1977). Thus the patching and capping phenomena could be looked at as part of a transmembranal information system which may trigger intracellular events at the moment of adsorption of a multivalent ligand to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…After 20 rain of exposure of normal rat kidney or WI38 human cells to Con A or to antibodies directed against different integral proteins, the binding of these reagents to their respective receptors at the cell surface has been shown to induce these receptors to redistribute to a limited extent into patches situated at the cell surface (Ash and Singer, 1976;Ash et al, 1977). By contrast, the binding of a multivalent ligand to its specific receptors on the surface of many cell in suspension, including lymphocytes, results first in a clustering of the receptors in small patches at the cell surface and, then, aggregation of the patches into a single cap (reviewed in Ash et al, 1977).…”
Section: Possible Involvement Of Pp60~ In Endocytotic Processesmentioning
confidence: 99%
“…By contrast, the binding of a multivalent ligand to its specific receptors on the surface of many cell in suspension, including lymphocytes, results first in a clustering of the receptors in small patches at the cell surface and, then, aggregation of the patches into a single cap (reviewed in Ash et al, 1977). Ash et al suggested that the ligand receptor patches were immobilized as a result of their association to stress fibers underlying the plasma membrane in fibroblasts, whereas, in lymphocytes, which do not possess stress fibers, such patches may move in the plane of the membrane and collect into a cap.…”
Section: Possible Involvement Of Pp60~ In Endocytotic Processesmentioning
confidence: 99%
“…For confocal analysis, cells were ®xed with 3.7% formaldehyde in PBS for 10 min, permeabilized with 0.2% Triton X-100 in PBS for 5 min and labeled with 7-aminoactinomycin D (Sigma). Cells were also labeled with two antibodies that recognize the endoplasmic reticulum (ER): anti-ER (Ash et al, 1977) and anti-PDI (Huovila et al, 1992), that were visualized with TRITC. Coverslips were mounted with Mowiol and analysed on a confocal microscope CLSM (Leica), with an argon-krypton laser (488 nm, 568 nm); for FITC a narrow-band ®lter centered on 535 nm+8 nm, line 488 nm; and for TRITC a long wave pass ®lter RG 590 nm, line 568 nm were used.…”
Section: Plasmid Constructsmentioning
confidence: 99%